Qadhi Legitimization: Shifting Roles of the Penghulu in Ternate and Tidore Sultanates, Indonesia - Fatum Abubakar,; Syahrul Mubarak Subeitan,; Abdul Rahim Hakimi,; Muhammad Faisol,; Siti Barora Sinay, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
The aim of this study is to analyze the shifting roles of penghulu in Ternate and Tidore Sultanates with a focus on the legal, social, and administrative changes influenced by government regulations and societal dynamics. A sociological-legal method was adopted with the data collected from penghulu, law enforcement officers, and local community members through in-depth interviews. Moreover, a purposive sampling strategy was used to ensure the inclusion of diverse relevant perspectives. The data were analyzed qualitatively by integrating two main theories. The first was M. Friedman's Legal System Theory applied to examine the legal foundations associated with the shifting roles of penghulu. The second was Shlomo Eisenstadt's Theory of Social Change which was used to understand the social change patterns due to the implementation of state regulations. The results showed that changes in the performance and discipline of the legal structure, as well as the legal substance and culture within the Ternate and Tidore Sultanates weakened traditional legal legitimacies. This shift led to a transformation in the social role of the penghulu who previously played a central role in marriage and inheritance law but no longer holds primary responsibility. The trend reflects a shift in societal orientation from adherence to Sultanate rules to compliance with state administration. The formal role of the penghulu diminished but the functions were continued informally in unregistered (sirri) marriages and remain recognized as a legal authority within the community. These results offer important insights into legal pluralism in postcolonial Islamic societies of Indonesia